Orientation‐Dependent Upper Critical Magnetic Field and Density of State for Uranium Ditelluride - Habtamu Anagaw Muluneh (Advanced Physics Research)
Abstract The superconductor UTe2 has garnered considerable attention due to its unique spin‐triplet pairing and high upper critical magnetic field, making it a promising candidate for exploring unconventional superconductivity. This study presents a theoretical investigation into the angle dependence of the upper critical magnetic field HC2 and the temperature‐dependent density of states (DOS) within UTe2. By employing anisotropic Ginzburg–Landau theory alongside microscopic modeling, the orientation‐dependent behavior of HC2 is analyzed along key crystallographic axes, particularly the a‐, b‐ and c‐axes, which demonstrate critical fields of ≈7, 15, and 11 T respectively. These results indicate a strong anisotropy in HC2, with a peak along the b‐axis, suggesting a profound alignment effect of the spin‐triplet pairs with the magnetic field. Additionally, temperature‐dependent DOS calculations reveal a pronounced increase in states near the Fermi level at lower temperatures, supporting the presence of unconventional pairing with potential nodal gaps. These findings suggest a complex interplay between spin fluctuations and electronic correlations, contributing to the robust superconducting phase in UTe2 and also provides deeper insights into the mechanisms driving superconductivity in UTe2 and highlights its potential for applications requiring high‐field superconductors.